USING "FIELD SUSTAINABILITY SOUNDING" METHOD FOR DETERMINATION THE POSSIBLE DEPTHS OF GROUNDWATER HORIZONS (Proceedings of the YSU C: Geological and Geographical Sciences, 2019)
Groundwater flows forming in the south-western slopes of the Geghama Ridge are mostly transported and unloaded in the well-known groundwater basin of Katnaghbyur in Kotayk Marz of the Republic of Armenia. The article presents the results of electrical exploration studies. The depths of groundwater were determined by "Field Sustainability Sounding" method. The "PODBOR-4" computer program was used for interpretation of aforecited FSS field data.
Keywords: underground basin; watercourse; waterproof layer; cracked lava; electric sounding method; graphs; receiver device (PDI); water horizon